2005
DOI: 10.1038/sj.ijo.0802954
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and obesity associated with a missense polymorphism in fatty acid amide hydrolase (FAAH)

Abstract: BACKGROUND: The brain endogenous cannabinoid system modulates reward and craving pathways and consequently may affect body weight. A naturally occurring missense polymorphism in the gene encoding fatty acid amide hydrolase (FAAH), the primary enzyme for inactivation of endocannabinoids, is associated with problem drug use. AIMS: To investigate the relationship between the FAAH cDNA 385 A/A (P129T) polymorphism and overweight disorders in subjects of multiple ethnic backgrounds attending a medical screening cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
177
2
12

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(199 citation statements)
references
References 36 publications
8
177
2
12
Order By: Relevance
“…12 Moreover, a recent study has shown that overweight and obesity are associated with a potential genetic malfunction of the fatty acid amide hydrolase (FAAH), one of the endocannabinoid degrading enzymes, further substantiating the hypothesis of a hyperactive endocannabinoid system as a possible cause of obesity. 8 To date we have no evidence of mRNA CB1-receptor stability or protein expression levels in A-allele carriers but the significant association of the presence of the polymorphic variant to a lower BMI is an intriguing issue. Moreover, Ravinet et al 5 found that CB-1 gene-deficient mice were lean and resistant to diet-induced obesity and showed reduced plasma insulin and leptin levels.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…12 Moreover, a recent study has shown that overweight and obesity are associated with a potential genetic malfunction of the fatty acid amide hydrolase (FAAH), one of the endocannabinoid degrading enzymes, further substantiating the hypothesis of a hyperactive endocannabinoid system as a possible cause of obesity. 8 To date we have no evidence of mRNA CB1-receptor stability or protein expression levels in A-allele carriers but the significant association of the presence of the polymorphic variant to a lower BMI is an intriguing issue. Moreover, Ravinet et al 5 found that CB-1 gene-deficient mice were lean and resistant to diet-induced obesity and showed reduced plasma insulin and leptin levels.…”
Section: Discussionmentioning
confidence: 96%
“…A recent study has shown that overweight and obesity are associated with a potential genetic malfunction of one of the endocannabinoid degrading enzymes, further substantiating the hypothesis of a hyperactive endocannabinoid system as a possible cause of obesity. 8 A silent intragenic biallelic polymorphism (1359G/A) of the CB1 gene (CNR1, X54937 GenBank accession number), resulting in the substitution of G to A at nucleotide position 1359 in codon 435 (Thr), was reported as a common polymorphism in the German population, 9 reaching frequencies of 24-32% for the rarer allele (A).…”
Section: Introductionmentioning
confidence: 99%
“…A genetic polymorphism of one of the enzymes responsible for EC breakdown (FAAH) has been linked with overweight and obesity in both white and black subjects. 61 A mutation in FAAH was also shown to influence lipid changes after a low-fat diet in obese subjects. 62 Furthermore, single-nucleotide polymorphisms of the gene encoding CB1 receptor have been shown to be associated with BMI and fat distribution in two independent samples of adult white European men.…”
Section: Human Datamentioning
confidence: 99%
“…3,5 In addition, the recent finding of a missense polymorphism in an endocannabinoid degrading enzyme, the fatty acid amide hydrolase (FAAH), associated with overweight and obesity supports the notion that the endocannabinoid system is upregulated in obesity. 2,6 On the basis of this background, the objective of the present study was to investigate the associations between the levels of AEA, 2-AG, OEA and PEA and body fat distribution assessed by computed tomography (intra-abdominal and subcutaneous adipose tissue (AT)) in a sample of nondiabetic men covering a wide range of adiposity values.…”
Section: Introductionmentioning
confidence: 99%